Computational dertermination of protonation for aromatic derivatives - Le, Minh Tam; Le, Hung Thanh; Nguyen, Tien Giang (Journal of Technical Education Science, 2023)
Protonation is an important process relating to various fields, such as biological reactions, and organic chemical synthesis. The determining position of protonation has been involved many challenging issues which are usually impossible to directly predict the positions of attaching protons from structures of molecules. However, predicting positions of protonation for aromatic rings is particularly important since it decides which form is preferred in the main products. For this reason, solving this task has been interesting for chemists since last decades with various studies carried out. Many results have been achieved in this field from both experimental and computational efforts. In the present work, protonation of three aromatic derivatives were investigated via the computational approach in which geometry configuration of relevant protonated molecules were optimized using the molecular modeling method. The results showed that protonation was strongly influenced when groups OH-, CH3-, and NH2- appear in aromatic derivatives with three cases studied including phenol, aniline and toluene.